gallitis and granulomatous colitis (Crohn’s disease): Presentation of three cases - Puig, Roberto; F. Cassinelli, Juan; Reissenweber, Nelson; P. Otero, Jose; Asiner, Boris; Balboa, Oscar (Cirugía del Uruguay, 1971)
Granulomatous ileitis and colitis is presented through a limited bibliographk revision. Three cases of Crohn's disease are presented: acute terminal ileitis, extensive ileocolitis and segmentary isolated colitis.